2014
DOI: 10.1021/ja413131m
|View full text |Cite|
|
Sign up to set email alerts
|

Nickel-Catalyzed Site-Selective Alkylation of Unactivated C(sp3)–H Bonds

Abstract: The direct alkylation of unactivated sp(3) C-H bonds of aliphatic amides was achieved via nickel catalysis with the assist of a bidentate directing group. The reaction favors the C-H bonds of methyl groups over the methylene C-H bonds and tolerates various functional groups. Moreover, this reaction shows a predominant preference for sp(3) C-H bonds of methyl groups via a five-membered ring intermediate over the sp(2) C-H bonds of arenes in the cyclometalation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 279 publications
(76 citation statements)
references
References 100 publications
3
72
0
1
Order By: Relevance
“…This is in agreement with similar Pd-catalyzed reactions where bis-arylation is occasionally observed [93]. Alkyl halides can also serve as electrophiles for these reactions, although a bidentate phosphine ligand is required [95]. Finally, rather than coupling to external electrophiles, Ge found that cyclization can occur to provide b-lactam products when TEMPO is used as an oxidant [96].…”
Section: Nickel Catalysissupporting
confidence: 84%
“…This is in agreement with similar Pd-catalyzed reactions where bis-arylation is occasionally observed [93]. Alkyl halides can also serve as electrophiles for these reactions, although a bidentate phosphine ligand is required [95]. Finally, rather than coupling to external electrophiles, Ge found that cyclization can occur to provide b-lactam products when TEMPO is used as an oxidant [96].…”
Section: Nickel Catalysissupporting
confidence: 84%
“…35 Ni(II) complexes were the preferred reagents and the optimized reaction conditions were [Ni(acac) 2 ] (10 mol %) with 1,2-bis(diphenylphosphino)benzene (dppbz) (10 mol %) as the ligand, alkyl halide (5 equiv), Cs 2 CO 3 (5 equiv) in toluene at 150°C for 1224 h (Scheme 13).…”
Section: Alkylationmentioning
confidence: 99%
“…As a synthetic application of this alkenylation, a highly functionalized carboxamide 53 was prepared via a sequence involving a Ni(II)-catalyzed arylation step, Ni(II)-alkenylation, hydrogenation under Pd/C, and Ni(II)-catalyzed alkenylation. [52]. In sharp contrast to the arylation of C(sp 3 )-H bonds [47], Ni(cod) 2 was not active as a catalyst.…”
Section: C-s Bond Formationmentioning
confidence: 92%